Doctors' opinions on clinical coordination between primary and secondary care in the Catalan healthcare system - Marta-Beatriz Aller; Ingrid Vargas; Jordi Coderch; Sebastià Calero; Francesc Cots; Mercè Abizanda; Lluís Colomés; Joan Farré; María-Luisa V (Elsevier, 2019)
Objective: To analyse doctors' opinions on clinical coordination between primary and secondary care in different healthcare networks and on the factors influencing it. Methods: A qualitative descriptive-interpretative study was conducted, based on semi-structured interviews. A two-stage theoretical sample was designed: 1) healthcare networks with different management models; 2) primary care and secondary care doctors in each network. Final sample size (n = 50) was reached by saturation. A thematic content analysis was conducted. Results: In all networks doctors perceived that primary and secondary care given to patients was coordinated in terms of information transfer, consistency and accessibility to SC following a referral. However, some problems emerged, related to difficulties in acceding non-urgent secondary care changes in prescriptions and the inadequacy of some referrals across care levels. Doctors identified the following factors: 1) organizational influencing factors: coordination is facilitated by mechanisms that facilitate information transfer, communication, rapid access and physical proximity that fosters positive attitudes towards collaboration; coordination is hindered by the insufficient time to use mechanisms, unshared incentives in prescription and, in two networks, the change in the organizational model; 2) professional factors: clinical skills and attitudes towards coordination. Conclusions: Although doctors perceive that primary and secondary care is coordinated, they also highlighted problems. Identified factors offer valuable insights on where to direct organizational efforts to improve coordination. Resumen: Objetivo: Analizar la opinión de los médicos sobre la coordinación entre la atención primaria (AP) y la atención especializada (AE) en diferentes redes de servicios de salud, e identificar los factores relacionados. Método: Estudio cualitativo descriptivo-interpretativo basado en entrevistas semiestructuradas. Se diseñó una muestra teórica en dos etapas: 1) redes de servicios de salud con diferentes modelos de gestión; 2) en cada red, médicos de AP y AE. El tamaño muestral se alcanzó por saturación (n = 50). Se realizó un análisis temático de contenido. Resultados: En las tres redes, los médicos expresaron que la atención está coordinada en términos de intercambio de información, consistencia y accesibilidad de AE tras derivación urgente. Sin embargo, emergieron problemas relacionados con el acceso no urgente y cambios en prescripciones, y en dos redes la inadecuación clínica de las derivaciones entre ambos niveles. Se identificaron los siguientes factores relacionados: 1) organizativos: facilitan la coordinación, la existencia de mecanismos de transferencia de información, de comunicación y de acceso rápido, y la proximidad física que promueve actitudes positivas a la colaboración; la obstaculizan el tiempo insuficiente para el uso de mecanismos, incentivos no compartidos en la prescripción y, en dos redes, un cambio del modelo organizativo; 2) relacionados con los profesionales: habilidades clínicas y actitudes frente a la coordinación. Conclusiones: Aunque los médicos perciben que la atención entre niveles está coordinada, también señalan problemas. Los factores identificados muestran hacia dónde dirigir los esfuerzos organizativos para su mejora. Keywords: Clinical coordination between care levels, Integrated health care, Interprofessional relations, Organizational models, Qualitative research, Palabras clave: Coordinación clínica entre niveles de atención, Prestación integrada de atención de salud, Relaciones interprofesionales, Modelos organizativos, Investigación cualitativa